Stochastic global optimization: techniques and applications in chemical engineering - Rangaiah, Gade Pandu (Advances in process systems engineering, 2010)
Optimization has played a key role in the design, planning and operation of chemical and related processes, for several decades. Global optimization has been receiving considerable attention in the past two decades. Of the two types of techniques for global optimization, stochastic global optimization is applicable to any type of problems having non-differentiable functions, discrete variables and/or continuous variables. It, thus, shows significant promise and potential for process optimization.